Suppression of Harmaline Tremor by Activation of an Extrasynaptic GABAA Receptor: Implications for Essential Tremor. (26th June 2018) - Handforth, Adrian; Kadam, Pournima A.; Kosoyan, Hovsep P.; Eslami, Pirooz
Background: Metabolic imaging has revealed excessive cerebellar activity in essential tremor patients. Golgi cells control cerebellar activity by releasing gamma-aminobutyric acid (GABA) onto synaptic and extrasynaptic receptors on cerebellar granule cells. We postulated that the extrasynaptic GABAA receptor-specific agonist THIP (gaboxadol; 4, 5, 6, 7-tetrahydroisoxazolo[5, 4-c]pyridin-3-ol) would suppress tremor in the harmaline model of essential tremor and, since cerebellar extrasynaptic receptors contain α 6 and δ subunits, would fail to do so in mice lacking either subunit. Methods: Digitally measured motion power, expressed as 10–16 Hz power (the tremor bandwidth) divided by background 8–32 Hz motion power, was accessed during pre-harmaline baseline, pre-THIP harmaline exposure, and after THIP administration (0, 2, or 3 mg/kg). These low doses were chosen as they did not impair performance on the straight wire test, a sensitive test for psychomotor impairment. Littermate δ wild-type and knockout ( Gabrd +/+, Gabrd –/– ) and littermate α 6 wild-type and knockout ( Gabra6 +/+, Gabra6 –/– ) mice were tested. Results: Gabrd +/+ mice displayed tremor reduction at 3 mg/kg THIP but not 2 mg/kg, and Gabra6 +/+ mice showed tremor reduction at 2 and 3 mg/kg. Their respective subunit knockout littermates displayed no tremor reduction compared with vehicle controls at either dose. Discussion: The loss of anti-tremor efficacy with deletion of either δ or α 6 GABAA receptor subunits indicates that extrasynaptic receptors containing both subunits, most likely located on cerebellar granule cells where they are highly expressed, mediate tremor suppression by THIP. A medication designed to activate only these receptors may display a favorable profile for treating essential tremor.